Role of Teacher Competence to Implement the Independent Curriculum - Pao P. Ruaya; He Xi Kang; Stephen Reader; Taufik Hidayat (Sultan Publisher, 2022)
This study aims to explore the teacher's role in the process of implementing the Independent Curriculum which has been implemented nationally through central government policies. In its implementation, the independent curriculum requires various adjustments to the social system and institutional support. This research uses a qualitative approach with a case study type. The results of the study show that the role of teacher competence is very important in the implementation of the independent curriculum, especially in achieving the expected educational goals and ideals. In addition, teachers as professional educators have a good role to play in guiding, motivating, and teaching students according to the needs and demands of the industrial revolution 4.0.